Statistical analysis of overnutrition student’s food consumption behavior at upper level of primary school in Kamphaeng Phet Province (Thailand) - Lalida Jamjumras (2018)
The purpose of this study was to compare the health belief and food consumption behavior between the pupils with normal nutritional status and those with overnutritional status, to identify the factors were related to food consumption behavior of the pupil and to find out the factors influencing the nutritional status of the pupil. The samples in this study were 258 pupils with normally nutritional status and 256 pupils with overnutritional status in the upper level of primary school in Muang district of Kamphaeng Phet Province in 2001. We used the questionnaire as a tool to search the health beliefs and food consumption behavior. All data were analyzed by using descriptive statistics and non-parametric statistics to test hypothesis about mean and the correlation between 2 variables. Category analysis was used to find the relationship between variable factors and food consumption behavior and we used logistic regression analysis to figure out which factors influencing the nutritional status of the pupils. At 0.05 level of significance, the pupils with normal nutritional status and those with overnutritional status had different health belief and food consumption behavior. Those with overnutritional status had improper food consumption behavior which were rapid as well as consumption of snack, fried food and soft drink. The factors having relationship with the food consumption behavior in normal nutritional status were health belief, gender and family income, where as the father’s education and drinking expense were related to food consumption behavior of the overnutritional status. The factors influencing the nutritional status were the health belief, food consumption behavior, the education of the father and mother. These factors could classify the nutritional status correctly about 77.08 percent of the pupils. © 2007, Taru Publications.